PERAN WORLD UYGHUR CONGRESS (WUC) DALAM MENGHADAPI PELANGGARAN HAM BERAT PADA ETNIS UYGHUR DI XINJIANG PADA TAHUN 2017-2020 - Nabila Tiara Putri; Muhammad Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This Study aims to explain WUC’s role in defending and voicing cases of discrimination that happened to Uyghurs. Discriminations is carried out by the Chinese government with gross human rights violations against ethnic Uyghurs such as freedom of speech, enjoing their own culture and freedon of religion. Many case of human rights violations, WUC as a Uyghur diaspora trying to tell this case to the international scope. This effort was made to help the Uyghurs regain their rights. This study discusses about the factors that cause discrimination and the policies of the Chinese government that cause human rights violations. This study uses qualitative methods, with data collection techniques through literature studies sourced from several books, journals, articles, websites. This study uses the perspective of Pluralism, the theory of international organizations. The results of this paper identify that the World Uyghur Congress (WUC) as an international organization of the Uyghur diaspora has tried and has been vocal in voicing cases of human rights violations against the Uyghur ethnicity so that it is widely known by the international community. Keywords: internasional organization, human rights, uyghurs, internasional organization, pluralism, WUC